Substantiation of the discharge mode of electrohydraulic equipment for drilling destruction of monolithic objects - V. O. Barsukov (Вестник СибАДИ, 2024)
Introduction. The article raises the problems associated with electrohydraulic drilling destruction of oversized monolithic objects, which are found, in particular, on the territory of construction works. At the moment, there is no assessment of the technology effectiveness, which means that methods are needed to justify the optimal discharge mode and its reproducibility in industrial equipment.   The purpose of the article is substantiation of optimal energy parameters for destructing monolithic objects by using electrohydraulic drilling method.   Materials and methods. The analysis of factors contributing to electrohydraulic fracture of monolithic objects was carried out and the most significant ones were identified. It is proposed to characterize the discharge mode with a set of parameters related to the transitional processes at the moments of conductor destruction, the discharge duration and the amount of energy input. Сalculation of the parameters has been presented in this paper.   Results and discussions. Based on the identified active factors, a stand for registration the electrohydraulic effect has been developed. Parameters for ensuring reproducibility of the discharge mode are derived depending on the change in the discharge circuit inductance. Practical implications are proposed based on data analysis.   Conclusion. The research findings advance a simple experiment planning to evaluate technology effectiveness. The article will be of interest to researchers in the field of electrohydraulic and electropulse technologies, and practitioners involved in clearing territories and removing monolithic objects.